Attitudes towards substance use and substance use disorders among medical students in Israel. (1st November 2016) - Lev-Ran, Shaul; Steinmetz, Yoed; Weiser, Mark
Abstract: Background : Negative attitudes towards substance use and Substance Use Disorders (SUDs) are among the commonly cited barriers to screening and treating these disorders by physicians. These negative attitudes have also been reported in medical students. The aim of this study was to examine attitudes of medical students in Israel towards nicotine, alcohol and drug use and SUDs based on their stage of training and personal experience. Methods : A sample of 329 medical students responded to the Attitudes Towards Substance Use questionnaire, which includes 50 questions regarding substance use and SUDs, as well as specific questions focusing on nicotine, alcohol, cannabis and heroin use. Results : Students at the clinical phase of their training had higher rates of moralism and lower rates of self-reported competency in treating SUDs compared to those in the pre-clinical phase of training. Personal experience with nicotine or alcohol use, as well as having a friend who suffers from addiction, were associated with lower rates of moralism. Across substances, the lowest ratings of treatment efficacy and of self-reported competence, were directed towards alcohol dependence. Conclusions : Medical education programs should include training in addiction medicine throughout all phases of medical school. This may have a significant role in future physicians' attitudes towards individuals with substance use and SUDs, and eventually in the treatment these patients receive.